2010
DOI: 10.1063/1.3494292
|View full text |Cite
|
Sign up to set email alerts
|

On Duffin–Kemmer–Petiau particles with a mixed minimal-nonminimal vector coupling and the nondegenerate bound-states for the one-dimensional inversely linear background

Abstract: The problem of spin-0 and spin-1 bosons in the background of a general mixing of minimal and nonminimal vector inversely linear potentials is explored in a unified way in the context of the Duffin-Kemmer-Petiau theory. It is shown that spin-0 and spin-1 bosons behave effectively in the same way. An orthogonality criterion is set up and it is used to determine uniquely the set of solutions as well as to show that even-parity solutions do not exist.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…We illustrate this equivalence by explicitly building the lowest dimensional (irreducible) representation of the theory. At the end we comment how our result explain why several authors in recent years found identical results for both the spin-0 and spin-1 sectors of the (3+1) dimensional DKP equation when the dynamics is restricted to only one space dimension [10][11][12][13][14][15][16][17][18][19][20] .…”
supporting
confidence: 64%
“…We illustrate this equivalence by explicitly building the lowest dimensional (irreducible) representation of the theory. At the end we comment how our result explain why several authors in recent years found identical results for both the spin-0 and spin-1 sectors of the (3+1) dimensional DKP equation when the dynamics is restricted to only one space dimension [10][11][12][13][14][15][16][17][18][19][20] .…”
supporting
confidence: 64%
“…From Eqs. ( 22), (23), and (29) we find H +1 , H −1 , G 0 in terms of F 0 . Then, we employ them in Eq.…”
Section: A (−1) J Parity Statessupporting
confidence: 54%
“…Then, by using the properties of vector spherical harmonics [2,7,23], we obtain the following radial differential equations:…”
Section: Dkp Equation In the Presence Of Minimum Uncertainty In Momentummentioning
confidence: 99%
See 1 more Smart Citation
“…Among the potentials used, we can highlight the double-step potential [16,17], the DKP oscillator [18,19], the inversely linear background [20], the mixed minimal-nonminimal vector cusp potential [21].…”
Section: Introductionmentioning
confidence: 99%